Framing Analysis of the Contents of Covid-19 Hoax News on the Kominfo.go.id Website - Habib Firmansyah; Anang Anas Azhar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Hoax content should have a lot of bad influences in the lives of individuals. The influence exerted in the news of a thing makes it easy for many people to believe before ascertaining the truth of the information. And information about covid-19 news is one of the content that is accompanied by a lot of hoax information. The mass media is one of the sources, this information grows and develops unstoppable, causing a lot of concern to the wider community. In this study, it provides an explanation of the news of covid-19 hoax content that has been sorted out as many as 242 cases by the Communication and Information Technology, and released in the news on the kominfo.go.id website on March 17, 2020. Framing analysis is the method used in this study, using the model of Zhongdang Pan and Gerald M. Kosicki through a constructive perspective. Research is carried out in order to understand the structure in reporting in the form of syntax, script, thematic, and rhetorical. How hoax content about Covid-19 can be very neatly controlled by Kominfo and produce valid information accompanied by attachment of content data that provides hoax information.